2010
DOI: 10.1590/s1519-566x2010000200016
|View full text |Cite
|
Sign up to set email alerts
|

Response of the predatory mite Phytoseiulus macropilis (Banks) to volatiles produced by strawberry plants in response to attack by Tetranychid mites (Acari: Phytoseiidae: Tetranychidae)

Abstract: -The attack of phytophagous mites may induce plants to produce volatiles, which in turn may attract predators. The occurrence of multiple phytophagous infestations on plants may infl uence predator response. In this paper, we investigated whether the attraction of the predatory mite Phytoseiulus macropilis (Banks) to phytophagous-infested plants would change with the simultaneous presence of two tetranichid mites Oligonychus ilicis (McGregor) and Tetranychus urticae Koch. While the former species is rarely fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(26 reference statements)
1
5
0
2
Order By: Relevance
“…The number of dead adult females was higher in pre-infested plants than in the clean plants ( Figure 1D, χ 2 =10.9, df=58, P<0.001). As demonstrated in the first part of the present investigation and in previous investigations SCHMELZ, 1996;FADINI et al, 2010a;PAULO et al, 2017), the pre-infestation of non-Bt maize plants by T. urticae reduced the survival and reproduction of the conspecific adult females, and it also reduces the survival of immatures. This suggests that maize plants which have undergone pre-infested by T. urticae altered the survival pattern of conspecific adult forms, reducing the performance of the population as a result of direct defense induction.…”
Section: Contentssupporting
confidence: 83%
“…The number of dead adult females was higher in pre-infested plants than in the clean plants ( Figure 1D, χ 2 =10.9, df=58, P<0.001). As demonstrated in the first part of the present investigation and in previous investigations SCHMELZ, 1996;FADINI et al, 2010a;PAULO et al, 2017), the pre-infestation of non-Bt maize plants by T. urticae reduced the survival and reproduction of the conspecific adult females, and it also reduces the survival of immatures. This suggests that maize plants which have undergone pre-infested by T. urticae altered the survival pattern of conspecific adult forms, reducing the performance of the population as a result of direct defense induction.…”
Section: Contentssupporting
confidence: 83%
“…Predatory mites are known to use volatiles to find their hosts (Janssen et al, 1997). For example, Y-tube olfactometer test assays demonstrated that predatory mites including Phytoseiulus persimilis (Athias and Henriot), Typhlodromus kerkirae (Swirski and Ragusa), Amblyseius womersleyi (Schicha), Phytoseiulus macropilis (Banks) have responded to volatiles from spider mites infested plants (Sabelis and van de Baan, 1983;Koveos and Broufas, 1999;Maeda et al, 2001;Fadini et al, 2010). Only one Y-tube study (Skelton et al, 2007) has been conducted using acarid mite, Tyrophagus putrescentiae (Schrank), which has contributed to the difficulties in designing appropriate bioassays.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the attraction of predatory mites Phytoseiulus macropilis (Banks) illustrates how an uncommon herbivore can interfere with a chemically mediated tritrophic interaction (Fadini et al . ). It was found that the predator was strongly attracted to plants with spider mites Tetranychus urticae , but avoided the odour of plants infested with red mites Oligonychus ilicis .…”
Section: Insects From the Third And Fourth Trophic Levelsmentioning
confidence: 97%
“…Doubly infested plants, carrying both herbivores, were not attractive to the predator, which supports the notion that interference in the chemical signalling by the unfamiliar herbivore may occur in this system (Fadini et al . ).…”
Section: Insects From the Third And Fourth Trophic Levelsmentioning
confidence: 97%